Relationship of nutritional status, risk for eating disorders and stress levels of university students - Wegner, Daniele Pereira; Bruch-Bertani, Juliana Paula (Disciplinarum Scientia | Saúde, 2025)
Introduction: Students tend to trigger problems related to the presence of stress and consequently the development of eating disorders (ED), reflecting on their nutritional status. Objective: To evaluate the relationship between nutritional status, risk for eating disorders and stress levels of university students. Methodology: Quantitative cross-sectional study carried out with university students aged over 18 years, enrolled in undergraduate courses at a Higher Education Institution. Using the Google Forms® tool, the Eating Attitudes Test (EAT-26) questionnaire was applied, which assesses the risk of developing ED and the Perceived Stress Scale (PSS-10) to assess perceived stress, in addition to weight and height data for nutritional status assessment, classified according to World Health Organization (WHO, 1998) for adults and PAHO (2002) for the elderly. The results were considered significant at a maximum level of significance of 5% (p <0.05). Results: Of the 82 university students, 92.7% were female, with a mean age of 23.7 ± 7.3 years, and 70.7% were classified as eutrophic. There was no relationship between nutritional status and risk for ED, however 77.1% of eutrophic university students presented risk for ED. Students with a high-risk stress level were associated with the presence of ED risk (p <0.05). Conclusion: The high-risk stress level was associated with the presence of ED risk and most of the participants in eutrophy presented a higher level of perceived stress.